Do significant immigrant inflows create negative education impacts? Lessons from the North Carolina public school system - Timothy M. Diette; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2012)
The influx of immigrants has shifted the ethnic composition of public schools in many states. Given the perceived negative impact of significant immigrant inflows, we are interested in investigating if these inflows into a school affect the academic performance of native students who remain. To address this question, we analyze education data from North Carolina, a state that has experienced a significant immigrant influx in the last two decades. We focus on the share of the English Language Learners in the student population for students between fourth and eighth grade over the period from 1999 to 2006 and the potential effects of the presence of these students on the level of achievement in math and reading for native students. Our analysis suggests some evidence of immigrant peer effects though the effects are heterogeneous. Specifically, we find some evidence of positive effects among those in the middle and bottom portions of the achievement distribution while we find small negative effects at the top of the distribution.
urn:nbn:de:101:1-201301213207
Keywords: I20; I21; J15; J24; 330; immigrants; student achievement; peer effects; education; Migranten; Bevölkerung; Bildungsniveau; Soziale Gruppe; Allgemeinbildende Schule; North Carolina